ความสวยงามวางนัยทัวไป: ผลคูณของสองจานวนที่ทุกหลักเป็นเลข 1 - Jaiorn, Yotin; Ngamsong, Yuwaret; Iampan, Aiyared (Naresuan University Journal: Science and Technology (NUJST), 2014)
บทความนี้นำเสนอการศึกษาและการหารูปทั่วไปของผลคูณของจำนวน n หลักที่ทุกหลักเป็นเลข 1 กับจำนวน m หลักที่ทุกหลักเป็นเลข 1 โดยที่ ผลการศึกษาพบรูปทั่วไปของผลคูณดังกล่าว ดังนี้   คำสำคัญ: ผลคูณ จำนวนที่ทุกหลักเป็นเลข 1 This paper presents the study and finding on a general form of a product of the n -digit number that every digit is 1 and the m -digit number that every digit is 1 where The results show that a general form of the product is Keywords: product, number that every digit as 1
Keywords: ผลคูณ จำนวนที่ทุกหลักเป็นเลข 1 product, number that every digit as 1